Asymmetric responses of spatial variation of different communities to a salinity gradient in coastal wetlands. (June 2020) - Li, Xiaoxiao; Yang, Wei; Li, Shanze; Sun, Tao; Bai, Junhong; Pei, Jun; Xie, Tian; Cui, Baoshan
Abstract: Various ecological communities are susceptible to the salinity gradients in coastal wetlands. Remane diagram has well described the macrozoobenthos diversity pattern along salinity gradients. Yet, further research is still needed, that is, the changes in diversity and biomass of other communities (e.g. plants, fish) along salinity gradients, and whether these changes are consistent or different among different communities. In this study, using China's Yellow River Delta wetland as a case study, we analyzed the variation of the community composition, species richness, and biomass of plant, macrozoobenthos, and fish communities along a salinity gradient from <0.5 to 30 ppt. We found that plant community composition exhibited more distinct variation along the salinity gradient than macrozoobenthos, with the least distinction for fish. Plant species richness decreased greatly along the gradient, whereas macrozoobenthos richness first decreased and then increased with increasing salinity, with the low richness occurring at a salinity of 0.9–12.3 ppt. Fish had the highest richness at a salinity of 14.8–16.0 ppt. The sum of plant, macrozoobenthos, and fish species and macrozoobenthos richness were both similar to the Remane diagram. Plants had higher biomass in low-salinity zones than in high-salinity zones, except for high biomass at a salinity of 14.8–16.0 ppt, whereas macrozoobenthos and fish showed the opposite trend. Principal-coordinate analysis showed an obvious dissimilarity map based on the composition, richness, and biomass of the plant, macrozoobenthos, and fish communities. Overall, the effects of salinity gradient differed among different communities. These findings demonstrate the asymmetric responses of different communities to salinity gradients, and have practical implications for maintaining a salinity gradient in coastal wetlands. Highlights: We studied spatial variation of plant, macrozoobenthos, and fish communities on a salinity gradient. All communities showed high variation along the salinity gradient. The salinity gradient's effects differed among different communities. The plant composition varied most along the salinity gradient. The trends of species richness and biomass of different communities along the salinity gradient are different.